Uniform corrosion assessment in oil and gas pipelines using corrosion prediction models – Part 1: models performance and limitations for operational field cases - Bachega Cruz, João Pedro; Veruz, Edilson Gabriel; Aoki, Idalina Vieira; Schleder, Adriana Miralles [UNESP]; de Souza, Gilberto Francisco Martha; Vaz, Gustavo Leitão; de Barros, Leonardo Oliveira; Orlowski, Rene Thiago Capelari; Martins, Marcelo Ramos (Elsevier, 2022)
Internal and uniform corrosion caused by the presence of corrosive gases CO2 and/or H2S in the inner stream is the major inherent concern of the oil and gas industry regarding its carbon steel pipelines selected for the processes present in hydrocarbons production and transportation, which culminates in generalized loss of thickness along the pipelines surface. Distinct corrosion predictive models have been developed and updated for the prediction of this corrosive mechanism through main multiphase flow physical-chemical parameters, however, worries regarding models’ uncertainties and limitations remains. This study reviews and compares the most common predictive models in the industry, clarifying its classifications and input parameters. Based on that, NORSOK, OLI and Predict models are applied to oil and gas operational field cases from literature and the implementation of a preliminary sensitivity analysis of models’ parameters for these applications is done. The progress allowed the operational cases histories evaluation and the elucidation of the main constraints of corrosion data collection by industry and of predictive models application. Moreover, this study discusses preliminary perspectives about models’ uncertainty and presents the pH as the most important influential parameter in uniform corrosion prediction, forwarding the necessary future development for corrosion assessment in operational pipelines.
Keywords: Carbon steel pipelines; Case histories evaluation; Corrosion prediction models; Oil and gas industry; Sensitivity analysis; Uniform corrosion assessment